2009
DOI: 10.1088/0004-637x/703/2/1696
|View full text |Cite
|
Sign up to set email alerts
|

DISCERNING THE PHYSICAL ORIGINS OF COSMOLOGICAL GAMMA-RAY BURSTS BASED ON MULTIPLE OBSERVATIONAL CRITERIA: THE CASES OFz= 6.7 GRB 080913,z= 8.2 GRB 090423, AND SOME SHORT/HARD GRBs

Abstract: The two high-redshift gamma-ray bursts, GRB 080913 at z = 6.7 and GRB 090423 at z = 8.3, recently detected by Swift appear as intrinsically short, hard GRBs. They could have been recognized by BATSE as short/hard GRBs should they have occurred at z ≤ 1. In order to address their physical origin, we perform a more thorough investigation on two physically distinct types (Type I/II) of cosmological GRBs and their observational characteristics. We reiterate the definitions of Type I/II GRBs and then review the fol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
257
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(275 citation statements)
references
References 262 publications
(391 reference statements)
14
257
2
2
Order By: Relevance
“…Early hints to the existence of distinct populations of gamma-ray transients (e.g., Mazets et al 1981;Norris et al 1984), and at least two classes of short-hard (Type-I) & long-soft (Type-II) GRBs (Dezalay et al 1992) have now been extensively corroborated and confirmed by the prompt-emission data E-mail: amir@physics.utexas.edu (AS); nemiroff@mtu.edu (RJN) from independent gamma-ray detector missions (e.g., Kouveliotou et al 1993a;Gehrels, Ramirez-Ruiz & Fox 2009; or follow-up observations of the afterglows or host galaxies (e.g., Zhang et al 2009;Berger 2011Berger , 2014. Although the possibility of more than two classes of GRBs with distinct progenitors has been extensively discussed and considered (e.g., Horvath 1998;Mukherjee et al 1998;Hakkila et al 2001;Balastegui, Ruiz-Lapuente & Canal 2001;Hakkila et al 2004b;Horvath et al 2006;Gehrels et al 2006;Chattopadhyay et al 2007;Horvath et al 2008;Virgili, Liang & Zhang 2009;Gao, Lu & Zhang 2010;Horvath et al 2012;Levan et al 2014;Kbori et al 2014), it has remained a matter of debate and speculation to this date (e.g., Hakkila et al 2000cHakkila et al ,a,b, 2003Hakkila et al , 2004aShahmoradi 2013b;Zhang et al 2014;Levan et al 2014).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Early hints to the existence of distinct populations of gamma-ray transients (e.g., Mazets et al 1981;Norris et al 1984), and at least two classes of short-hard (Type-I) & long-soft (Type-II) GRBs (Dezalay et al 1992) have now been extensively corroborated and confirmed by the prompt-emission data E-mail: amir@physics.utexas.edu (AS); nemiroff@mtu.edu (RJN) from independent gamma-ray detector missions (e.g., Kouveliotou et al 1993a;Gehrels, Ramirez-Ruiz & Fox 2009; or follow-up observations of the afterglows or host galaxies (e.g., Zhang et al 2009;Berger 2011Berger , 2014. Although the possibility of more than two classes of GRBs with distinct progenitors has been extensively discussed and considered (e.g., Horvath 1998;Mukherjee et al 1998;Hakkila et al 2001;Balastegui, Ruiz-Lapuente & Canal 2001;Hakkila et al 2004b;Horvath et al 2006;Gehrels et al 2006;Chattopadhyay et al 2007;Horvath et al 2008;Virgili, Liang & Zhang 2009;Gao, Lu & Zhang 2010;Horvath et al 2012;Levan et al 2014;Kbori et al 2014), it has remained a matter of debate and speculation to this date (e.g., Hakkila et al 2000cHakkila et al ,a,b, 2003Hakkila et al , 2004aShahmoradi 2013b;Zhang et al 2014;Levan et al 2014).…”
Section: Introductionmentioning
confidence: 83%
“…cal classification of GRBs based on empirical relations that are believed to hold for only a specific class of GRBs or based on the prompt or afterglow emission data (e.g., Zhang et al 2009;L et al 2010;Qin & Chen 2013). These methods however, either suffer from sample incompleteness or require information, such as redshift, that might not be available for the majority of GRBs (e.g., Coward et al 2012Coward et al , 2013.…”
Section: Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central engine timescale (the accretion timescale in our example; Zhang et al 2009) can be constrained to be at most the observed duration or t acc 1 s (Aloy et al 2005). This constraint will carve out a region in Figure 2 to the left of the t acc =1 s or R out =2.3×10 8 cm line.…”
Section: Generic Blandford-znajek Scenariomentioning
confidence: 96%
“…The progenitors of long GRBs consist of supernovae related to the collapse of massive stars (Woosley & Bloom 2006) and those of short GRBs are thought to be binary compact object mergers (Nakar 2007). There are however exceptions to this general picture (Zhang et al 2009;Bromberg et al 2013).…”
Section: Introductionmentioning
confidence: 99%